Atmospheric pressure cold plasma (ACP) treatment of wheat flour. (February 2015) - Misra, N.N.; Kaur, Seeratpreet; Tiwari, Brijesh K.; Kaur, Amritpal; Singh, Narpinder; Cullen, P.J.
Abstract: Atmospheric pressure cold plasma (ACP) is an emerging advanced oxidation process which has recently drawn considerable interest from food scientists. The objective of this study was to investigate the effect of ACP treatments on the properties of hard and soft wheat flour. Optical emission characterisation of the dielectric barrier discharge ACP source and ozone measurements revealed the generation of reactive oxygen and excited nitrogen species. The rheological properties of flours were studied using mixogram and oscillation rheometry. Mixographs revealed an improvement in the dough strength and optimum mixing time for both strong and weak wheat flours. The elastic and viscous moduli of strong wheat flour progressively increased with applied voltage and treatment time. A significant variation in the tan δ was not found. Changes in the secondary structure of proteins were evaluated using FTIR spectroscopy and revealed a decrease in β-sheets and increase in α-helix and β-turns, for both strong and weak wheat flour. The results indicate that ACP can be exploited as a means to modulate functionality of wheat flour. Graphical abstract: Highlights: Atmospheric pressure cold plasma (ACP) treatment effects on flour quality were evaluated. ACP effects on rheological properties were evaluated using Mixograph and Dynamic rheometry. Changes caused by ACP in secondary structures of dough proteins were assessed. Optimum conditions to obtain desirable effects of ACP of dough vary with wheat type.